2020
DOI: 10.31577/ahs-2020-0021.01.0007
|View full text |Cite
|
Sign up to set email alerts
|

Impact of different proportion of agricultural land in river catchments on nitrogen surface streams pollution

Abstract: Water quality is threatened particularly in regions where the agricultural landscape is prevailing. This study presents results of the comparison of yearly total nitrogen emissions and contribution of different emission pathways on this emissions into surface streams for three river catchments in Slovakia territory with the contrasting proportion of agricultural land to the total area of the river catchment. For nitrogen yearly emissions and pathways detection, the numerical model MONERIS has been used. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The relation between discharge and nitrate concentration was used to derive exponential empirical relations for estimating the nitrate-nitrogen concentrations in the stream based on mean daily discharge. Siman and Velísková (2020) presented results of the comparison of yearly total nitrogen emissions and the contribution of different emission pathways on these emissions into surface streams for three river catchments in Slovakia territory with a contrasting proportion of agricultural land to the total area of the river catchment using the numerical MONERIS model. Results indicated that in river catchments with a higher proportion of agricultural land, higher contribution of nitrogen emission was carried out mainly via groundwater (especially in lowland) and agricultural erosion and drainage systems.…”
Section: Erosion Sediment Transport River Morphology and Hydro-ecologymentioning
confidence: 99%
“…The relation between discharge and nitrate concentration was used to derive exponential empirical relations for estimating the nitrate-nitrogen concentrations in the stream based on mean daily discharge. Siman and Velísková (2020) presented results of the comparison of yearly total nitrogen emissions and the contribution of different emission pathways on these emissions into surface streams for three river catchments in Slovakia territory with a contrasting proportion of agricultural land to the total area of the river catchment using the numerical MONERIS model. Results indicated that in river catchments with a higher proportion of agricultural land, higher contribution of nitrogen emission was carried out mainly via groundwater (especially in lowland) and agricultural erosion and drainage systems.…”
Section: Erosion Sediment Transport River Morphology and Hydro-ecologymentioning
confidence: 99%
“…However, its acceleration is most often caused by human activity in the countryside, and this causes problems that must be solved (Podhrádzka, 2010;Petlušová et al, 2017). It was confirmed that by soil erosion there are transported soil sediment and nitrogen which contributes to surface water contamination (Siman and Velisková, 2020). Therefore, the rural landscape has become the subject of our interest.…”
Section: Introductionmentioning
confidence: 98%
“…The siltation rate rose to 65 Mm 3 year -1 in 2017 which represents about 0.75% of the annual loss of dam capacity (Remini, 2017). In addition, the water erosion and sediment transport represent the first factor that reduces the fertility of agricultural land (Xiong et al, 2024), by leaching nitrogen that concentrates in surface water and leads to its pollution (Siman and Velisková, 2020, Kováčová, 2022, Kováčová, 2023. The sediment transported in streams is usually estimated at the gauging station using in situ measurements of suspended sediment concentration (Achite and Ouillon, 2007).…”
Section: Introductionmentioning
confidence: 99%